Air Pressure, Gas Exposure and Electron Beam Irradiation of 2D Transition Metal Dichalcogenides - Di Bartolomeo, Antonio; Pelella, Aniello; Grillo, Alessandro; Urban, Francesca; Giubileo, Filippo (Applied sciences, 2020)
In this study, we investigate the electrical transport properties of back-gated field-effect transistors in which the channel is realized with two-dimensional transition metal dichalcogenide nanosheets, namely palladium diselenide (PdSe2) and molybdenum disulfide (MoS2). The effects of the environment (pressure, gas type, electron beam irradiation) on the electrical properties are the subject of an intense experimental study that evidences how PdSe2-based devices can be reversibly tuned from a predominantly n-type conduction (under high vacuum) to a p-type conduction (at atmospheric pressure) by simply modifying the pressure. Similarly, we report that, in MoS2-based devices, the transport properties are affected by pressure and gas type. In particular, the observed hysteresis in the transfer characteristics is explained in terms of gas absorption on the MoS2 surface due to the presence of a large number of defects. Moreover, we demonstrate the monotonic (increasing) dependence of the width of the hysteresis on decreasing the gas adsorption energy. We also report the effects of electron beam irradiation on the transport properties of two-dimensional field-effect transistors, showing that low fluences of the order of few e-/nm2 are sufficient to cause appreciable modifications to the transport characteristics. Finally, we profit from our experimental setup, realized inside a scanning electron microscope and equipped with piezo-driven nanoprobes, to perform a field emission characterization of PdSe2 and MoS2 nanosheets at cathode–anode separation distances as small as 200 nm.